PENGGUNAAN MEDIA GAMBAR DAN PEMODELAN DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI - Hidayat, Firman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research is motivated by the low learning outcomes of students' writing descriptive essays, because their learning activities are limited to listening activities and doing practice questions. The use of media in learning is expected to improve students' writing skills. The researcher tested the use of image media and modeling in learning to write descriptive essays with the aim of describing the process and results of learning to write descriptive essays and describing students' perceptions of the media used in the study. The theoretical basis in this study includes the theory of learning media, and the theory of writing essays. This quasi-experimental study used a different group pre-test-post-test design. Based on the results of the comparison of the two classes, learning to write descriptive essays using modeling is more effective in improving descriptive essay writing skills compared to that using image media. Therefore, modeling is recommended to be one of the references in implementing and developing learning to write descriptive essays.